Handbook of greener synthesis of nanomaterials and compounds. - Kharisov, Boris I.; Kharissova, Oxana Vasilievna (Elsevier, 2021)
Modern techniques to produce nanoparticles, nanomaterials, and nanocomposites are based on approaches that frequently involve high costs, inefficiencies, and negative environmental impacts. As such, there has been a real drive to develop and apply approaches that are more efficient and benign. The Handbook of Greener Synthesis of Nanomaterials and Compounds provides a comprehensive review of developments in this field, combining foundational green and nano-chemistry with the key information researchers need to assess, select and apply the most appropriate green synthesis approaches to their own work. Volume 2: Synthesis at the Macroscale and Nanoscale explores synthesis at different scales. Beginning with a selection of chapters discussing a range of macroscale topics, the book goes on to explore such important areas as metal nanoparticle synthesis, biogenic synthesis, and synthesis of enzymes. Further chapters explore the role of Metal Organic Frameworks in greener synthesis, synthesis from renewable sources, and impacts of nanomaterials synthesized by greener methods.